El productor-experimentador (P-E) como estrategia para optimizar las tecnologias de unidades de produccion (UP) de pequenos productores (PP) - Villarreal F., E.; Galvan C., F. (International Center for Tropical Agriculture, 1987)
The technology transfer method used in Mexico by the Instituto Nacional de Investigaciones Agricolas, named producer-experimenter, is described. The exptl. results obtained with beans using this method are presented. From the 100 bean genotypes evaluated in monocropping, var. Canario 101, Flor de Mayo, Bayo Alteno, El Bayo Zacatecas, and Negro Jamapa have been accepted. For beans in association, late and climbing genotypes with grain and cooking quality similar to those of the landrace are preferred. From advanced generations and a combination of individual and massive selection, 2 lines have been obtained that satisfy requirements of plant cycle, plant type, load/plant, grain size, cooking time, and flavor; they will be screened for yields. From the joint analysis of exptl. data in communities and among them, mathematical models have been obtained that allow for a better understanding of the reality. (CIAT)